Consequences of a changing US strategy in the global HIV investment landscape. (28th November 2017) - McGillen, Jessica B.; Sharp, Alana; Honermann, Brian; Millett, Gregorio; Collins, Chris; Hallett, Timothy B.
Abstract : Objective: The global fight against HIV/AIDS in Africa has long been a focus of US foreign policy, but this could change if the federal budget for 2018 proposed by the US Office of Management and Budget is adopted. We aim to inform public and Congressional debate around this issue by evaluating the historical and potential future impact of US investment in the African HIV response. Design/methods: We use a previously published mathematical model of HIV transmission to characterize the possible impact of a series of financial scenarios for the historical and future AIDS response across Sub-Saharan Africa. Results: We find that US funding has saved nearly five million adults in Sub-Saharan Africa from AIDS-related deaths. In the coming 15 years, if current numbers on antiretroviral treatment are maintained without further expansion of programs (the proposed US strategy), nearly 26 million new HIV infections and 4.4 million AIDS deaths may occur. A 10% increase in US funding, together with ambitious domestic spending and focused attention on optimizing resources, can avert up to 22 million HIV infections and save 2.3 million lives in Sub-Saharan Africa compared with the proposed strategy. Conclusion: Our synthesis of available evidence shows that the United States has played, and could continue to play, a vital role in the global HIV response. Reduced investment could allow more than two million avoidable AIDS deaths by 2032, whereas continued leadership by the United States and other countries could bring UNAIDS targets for ending the epidemic into reach. Abstract : Supplemental Digital Content is available in the text